2010
DOI: 10.1111/j.1399-3038.2010.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a partially hydrolysed formula based on rice protein in the treatment of infants with cow’s milk protein allergy

Abstract: Reche M, Pascual C, Fiandor A, Polanco I, Rivero-Urgell M, Chifre R, Johnston S, Martín-Esteban M. The effect of a partially hydrolysed formula based on rice protein in the treatment of infants with cow’s milk protein allergy. Pediatr Allergy Immunol 2010: 21: 577–585. © 2010 John Wiley & Sons A/SInfants diagnosed with allergy to cow’s milk protein (CMP) are fed extensively hydrolysed cow’s milk formulas, modified soy formulas or even amino acid-based formulas. Hydrolysed rice protein infant formulas have beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
1
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 24 publications
1
77
1
10
Order By: Relevance
“…5 Other studies have addressed the potential effects of formula selection on the natural history of CM allergy, but pHWFs were not specifically examined. 2, 6, 7 pHWF may carry unique immunoregulatory characteristics. 8,9 …”
mentioning
confidence: 99%
“…5 Other studies have addressed the potential effects of formula selection on the natural history of CM allergy, but pHWFs were not specifically examined. 2, 6, 7 pHWF may carry unique immunoregulatory characteristics. 8,9 …”
mentioning
confidence: 99%
“…The first study, published in 2010 by Reche et al, compared the clinical tolerance of a hydrolyzed rice protein formula with an extensively hydrolyzed cow’s milk formula (EHCF) in infants with IgE-mediated cow’s milk allergy. The authors found no significant differences regarding tolerance achievement, adverse reactions, sIgE level, growth, or clinical tolerance 101. In a 2013 trial comparing five feeding regimens in milk-allergic children (EHCF, EHCF + Lactobacillus rhamnosus GG, hydrolyzed rice formula, soy formula, and amino acid formula), milk-allergic children who received EHCF alone or in combination with L. rhamnosus GG achieved tolerance at 12 months.…”
Section: Methodsmentioning
confidence: 94%
“…Anne sütü almayan bebeklerde inek sütü proteini içermeyen mamaların kullanı-mı önerilmektedir. Bu amaçla AAF, yarı hidrolize mamalar, tam hidrolize mamalar (eHF), soya bazlı mamalar ve pirinç bazlı mamalar kullanılmaktadır [22]. Sadece AAF non-alerjiktir.…”
Section: Tedavi̇ Ve İzlemunclassified